Anaemia and Caesarean Section in Caucasian Race: Assessment of Risk Factors and Management Strategies - Khakpour, Yaser; Moradi Heidarlou, Mahshid; Shukohi, Shahram; Akbari, Mahla (Universitas Ahmad Dahlan, 2025)
Background: Anaemia among pregnant women is a significant public health concern, particularly in developing countries, due to its adverse effects on both maternal and fetal health. This study addresses the gap in research regarding anaemia in pregnant women in northern Iran, specifically among those undergoing elective caesarean sections. The objective is to assess the prevalence of anaemia in this population. Method: This retrospective cross-sectional study included 719 Caucasian pregnant women who were candidates for elective caesarean sections from September 2020 to March 2023. Patient data was collected from hospital electronic records. Anaemia was defined as haemoglobin <10.5 g/L in the three months before delivery and under 10 g/L after delivery. The Chi-square test was employed to compare anaemia prevalence across different demographic groups, with a significance level set at p-value < 0.05. Results: Among the 719 participants, key demographic findings revealed that most had primary education (26.8%), while only 12.4% held university degrees. Most (59.8%) resided in urban areas, with the largest age group being 31-36 (30.5%). Most women (75.2%) reported no history of miscarriage, and 98.2% experienced no bleeding during pregnancy. Notably, 57.7% of women reported no underlying health conditions; however, 9.2% had gestational diabetes, while others had blood disorders, neurological issues, or gastrointestinal problems. The prevalence of anaemia among patients undergoing elective caesarean sections was found to be 10.85%. Anaemia was more prevalent in women aged 25-30 years. Conclusion: integrating nutritional counselling into routine prenatal care can help address dietary deficiencies before they contribute to anaemia. Moreover, collaboration between healthcare providers and community leaders may foster greater acceptance of health interventions. By tailoring educational programs to local contexts and addressing specific cultural beliefs about nutrition and health, policymakers can create more effective strategies to combat anaemia in pregnant women.